Asymmetric Catalysis from a Chinese Perspective - Ma, Shengming; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
Qi-Lin Zhou and Jian-Hua Xie: Chiral Spiro Catalysts.- Fuk Loi Lam, Fuk Yee Kwong and Albert S. C. Chan: Chiral Phosphorus Ligands with Interesting Properties and Practical Applications.- Jiang Pan, Hui-Lei Yu, Jian-He Xu, Guo-Qiang Lin: Advances in Biocatalysis: Enzymatic Reactions and Their Applications.- Mei-Xiang Wang: Enantioselective Biotransformations of Nitriles.- Man Kin Wong, Yiu Chung Yip and Dan Yang: Asymmetric Epoxidation Catalyzed by Chiral Ketones.- W. J. Liu, N. Li and L. Z. Gong: Asymmetric Organocatalysis.- Qing-Hua Fan and Kuiling Ding: Enantioselective Catalysis with Structurally Tunable Immobilized Catalysts.- Chang-Hua Ding, Xue-Long Hou: Transition Metal-Catalyzed Asymmetric Allylation.- Jian Zhou and Yong Tang: Enantioselective Reactions with Trisoxazolines.- Xiang-Ping Hu, Duo-Sheng Wang, Chang-Bin Yu, Yong-Gui Zhou, and Zhuo Zheng: Adventure in Asymmetric Hydrogenation: Synthesis of Chiral Phosphorus Ligands and Asymmetric Hydrogenation of Heteroaromtics.
Qi-Lin Zhou and Jian-Hua Xie: Chiral Spiro Catalysts -- Fuk Loi Lam, Fuk Yee Kwong and Albert S. C. Chan: Chiral Phosphorus Ligands with Interesting Properties and Practical Applications -- Jiang Pan, Hui-Lei Yu, Jian-He Xu, Guo-Qiang Lin: Advances in Biocatalysis: Enzymatic Reactions and Their Applications -- Mei-Xiang Wang: Enantioselective Biotransformations of Nitriles -- Man Kin Wong, Yiu Chung Yip and Dan Yang: Asymmetric Epoxidation Catalyzed by Chiral Ketones -- W. J. Liu, N. Li and L. Z. Gong: Asymmetric Organocatalysis -- Qing-Hua Fan and Kuiling Ding: Enantioselective Catalysis with Structurally Tunable Immobilized Catalysts -- Chang-Hua Ding, Xue-Long Hou: Transition Metal-Catalyzed Asymmetric Allylation -- Jian Zhou and Yong Tang: Enantioselective Reactions with Trisoxazolines -- Xiang-Ping Hu, Duo-Sheng Wang, Chang-Bin Yu, Yong-Gui Zhou, and Zhuo Zheng: Adventure in Asymmetric Hydrogenation: Synthesis of Chiral Phosphorus Ligands and Asymmetric Hydrogenation of Heteroaromtics.
Keywords: Chemistry; Chemistry, Organic; Catalysis; Chemistry; Organometallic Chemistry; Catalysis; Organic Chemistry